1994
DOI: 10.1007/bf00327781
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of muscle hypertrophy in the rat urinary bladder after removal of urethral obstruction

Abstract: We studied the ultrastructure of the bladder musculature after first inducing hypertrophy by means of urethral obstruction and subsequently removing the obstruction. With hypertrophy the bladder musculature increases ten-fold or more in volume; after de-obstruction approximately 4/5 of the hypertrophic muscle weight and volume is lost within six weeks. In spite of this very large decrease in muscle mass there is no degeneration of muscle cells or nerve endings or of other cell types in the de-obstructed bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 18 publications
2
16
0
1
Order By: Relevance
“…Many clinicians favor decompressing the bladder for a week or more to improve the likelihood of a successful voiding trial 67 . Animal studies indicate that retention results in detrusor damage, collagen infiltration, and decreased contractility 47,70 . Many of these changes improve after relief of obstruction 70 .…”
Section: Management Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinicians favor decompressing the bladder for a week or more to improve the likelihood of a successful voiding trial 67 . Animal studies indicate that retention results in detrusor damage, collagen infiltration, and decreased contractility 47,70 . Many of these changes improve after relief of obstruction 70 .…”
Section: Management Issuesmentioning
confidence: 99%
“…Animal studies indicate that retention results in detrusor damage, collagen infiltration, and decreased contractility 47,70 . Many of these changes improve after relief of obstruction 70 . It has been proposed that bladder decompression may facilitate healing and promote the restoration of normal detrusor contractility.…”
Section: Management Issuesmentioning
confidence: 99%
“…With respect to the application of hSlo myocyte gene therapy to bladder function, one might not, at first glance, anticipate a similar degree of physiological success. One obvious reason for skepticism is related to the apparent absence of the morphological and structural correlates of gap junctions in human (18,21) and rat bladder (28,29). In this regard, a recent report has shown that mRNA for the gap junction protein Cx43 can be detected in the normal rat bladder using RT-PCR techniques (16).…”
Section: Why Does Gene Therapy With Hslo Ameliorate Bladder Overactivmentioning
confidence: 99%
“…Clinical treatments focus on mitigating the source of out‐flow obstruction, yet removal of the anatomical PBO itself does not completely reverse the pathology and dysfunction, in a large proportion of BPH and PUV patients, even months or years following REL. The failure to resolve after REL is seen at multiple levels (matrix, neural input, and smooth muscle cellular phenotype) and leads to ongoing sequelae such as increased residual volumes and altered activity …”
Section: Introductionmentioning
confidence: 99%